PEMBUATAN ALAT UKUR SALINITAS DAN KEKERUHAN AIR MENGGUNAKAN SENSOR ELEKTRODA DAN LDR - Siltri, Dina Mulya; Yohandri, Yohandri; Zulhendri Kamus, Zulhendri Kamus (IAIN Batusangkar, 2015)
The objective of this research is to determine both performance and design spesification of Salinitymeter and Turbiditymeter. This system combined from several sub systems such as electrode and Light Dependent Resistor (LDR) sensor, microcontroller Arduino, Liquid Crystal Display (LCD) and Light Emiting Diode (LED) indicators. The variable of this research are salinity and turbidity. The result of this research divided in two parts. The first is performance spesification, this system using copper electrode as salinity sensor and LDR as turbidity sensor. This consist of two plastic box which are circuit box and sample box. The second is design spesification that consist of some data such as accuration and precision. Salinity measurement has accuration 95.71% with precision 97.22%, Turbidity measurement has 96.25 % of accuration and 97.69% of precision.Key words: salinity, turbidity, electrode sensor